Multifunctional intracellular matrix metalloproteinases: implications in disease - Bassiouni, Wesam; Ali, Mohammad A. M.; Schulz, Richard (The FEBS journal, 2021)
Matrix metalloproteinases (MMPs) are zinc‐dependent endopeptidases that were first discovered as proteases, which target and cleave extracellular proteins. During the past 20 years, however, intracellular roles of MMPs were uncovered and research on this new aspect of their biology expanded. MMP‐2 is the first of this protease family to be reported to play a crucial intracellular role where it cleaves several sarcomeric proteins inside cardiac myocytes during oxidative stress‐induced injury. Beyond MMP‐2, currently at least eleven other MMPs are known to function intracellularly including MMP‐1, MMP‐3, MMP‐7, MMP‐8, MMP‐9, MMP‐10, MMP‐11, MMP‐12, MMP‐14, MMP‐23 and MMP‐26. These intracellular MMPs are localized to different compartments inside the cell including the cytosol, sarcomere, mitochondria, and the nucleus. Intracellular MMPs contribute to the pathogenesis of various diseases. Cardiovascular renal disorders, inflammation, and malignancy are some examples. They also exert antiviral and bactericidal effects. Interestingly, MMPs can act intracellularly through both protease‐dependent and protease‐independent mechanisms. In this review, we will highlight the intracellular mechanisms of MMPs activation, their numerous subcellular locales, substrates, and roles in different pathological conditions. We will also discuss the future direction of MMP research and the necessity to exploit the knowledge of their intracellular targets and actions for the design of targeted inhibitors. Matrix metalloproteinases (MMPs) were first discovered as secreted proteases that cleave extracellular matrix proteins. However, by different mechanisms, they can also remain inside the cell and localize to different subcellular compartments and organelles including, for example, the cytosol, mitochondria, nuclei, and sarcomere. When intracellularly activated, MMPs can also proteolyze specific intracellular proteins to affect both pathological and physiological responses.